Geoffrey Hartman: Romanticism after the Holocaust - Vermeulen, Pieter (Bloomsbury Publishing, 2010)
Geoffrey Hartman: Romanticism after the Holocaust offers the first comprehensive critical account of the work of the American literary critic Geoffrey Hartman. The book aims to achieve two things: first, it charts the whole trajectory of Hartman''s career (now more than half a century long) while playing close attention to the place of his career in broader cultural and intellectual contexts; second, it engages with contemporary discussions about ecology, ethics, trauma, the media, and community in order to argue that Hartman''s work presents a surprisingly consistent and original position in